Tamsulosin in the management of distal ureteric calculi - Thapa, Narayan; Bhandari, Bharat; Hamal, Bhairab Kumar (Journal of Patan Academy of Health Sciences, 2015)
Introductions: Ureteral stones account for 20% urinary stone. Two third of ureteral stones are seen in lower third of ureter. Medical expulsive therapy is effective for such stones. This study was designed to observe the efficacy of ‘tamsulosin’ a selective alpha-1 adrenoreceptor antagonist in the management of lower ureteric stone. Methods: A cross sectional study of 70 cases of distal ureteral stones of sizes 5 to 10 mm was taken in the Department of Surgery of Shree Birendra Hospital, Nepalese Army Institute of Health Sciences (NAIHS) from January 2011 to 2013. Patients were randomly divided into tamsulosin and analgesic only groups. Stone expulsion at the end of three weeks was confirmed by X-ray or Ultrasonography. Results: Out of 70 patients, stone clearance rate in tamsulosin group was 28 in 35 cases (80%) and 21 in 35 cases (60%) in group II with analgesic only. The mean time of stone expulsion was 8.3 days in group I and 13.5 days in group II. Conclusions: In this study the use of tamsulosin in treatment of lower ureteral stones less than 10 mm was safe and effective.